The Phenomenon of the Hijab Wrapping Tightly in the Qur'an Sunnah Review and its Comparison with the Veil and Burqa: Fenomena Berjilbab tapi Ketat dalam Tinjauan Qur’an Hadis dan Komparasinya pada Cadar, Niqab dan Burqa - Erma Rahmawati; Fikri Abdul Aziz; Gina Raudhatul Jannah (Bulletin of Islamic Research, 2024)
Islam sets various norms for its followers, including Muslim women, who are required to cover their aurat, maintain good character, and beautify their speech. Various types of coverings such as jilbab, hijab, khimar, niqab, and burqa serve the same function but have different forms. The niqab covers the face except for the eyes, while the burqa covers the entire face. Although modern technology makes it easier for Muslim women to choose comfortable and fashionable clothing, many prioritize trends over the function of covering the aurat. The interpretation of the Qur'an and Hadith regarding how to cover the aurat needs to be understood and applied correctly. This study uses an interpretative approach to understand tafsir literature. The hijab aims to protect women's dignity, and although slavery has been abolished, the hijab remains relevant to distinguish free women and maintain morality. The hijab controversy often arises due to differing interpretations of religion and gender. The majority of scholars agree that a woman's entire aurat should be covered except for the face and hands. This study provides an understanding of the meanings of hijab, niqab, and burqa and invites society, especially women, to understand and implement these teachings according to Sharia.